The Effect of Temperature and Extraction Time of Cinnamon (Cinnamomum burmannii) on Physicochemical and Organoleptic Properties of Herbal Paper Soap - N Narsih; Y. Erning Indrastuti; S Saniah; Borneo Satria Pratama; Desi Ramayanti (Demeter: Journal of Farming and Agriculture, 2024)
This study aims to examine the effects of cinnamon (Cinnamomum burmannii) extraction temperature and duration on the physicochemical and organoleptic characteristics of herbal paper soap. The experiment involved three extraction temperatures (60°C, 70°C, and 80°C) and two extraction durations (15 and 20 minutes), resulting in six treatment combinations. The findings indicate that an extraction temperature of 60°C for 15 minutes produced the best moisture content, and foam stability, while the optimal free alkali content was obtained at 80°C for 20 minutes. The highest antibacterial activity was observed at 70°C for 15 minutes. In the organoleptic evaluation, the best color scoring was achieved at 60°C for 20 minutes, aroma scoring at 80°C for 20 minutes, and thickness scoring at 60°C for 15 minutes. Further analysis revealed that extraction temperature and duration significantly influenced the physicochemical properties, including free alkali content, foam stability, and skin irritation, as well as organoleptic characteristics such as color, aroma, and thickness. However, these factors had no significant effect on moisture content and antibacterial activity. Overall, the paper soap met the quality standards outlined in SNI 06-3532-2016, except for free alkali content, which exceeded the maximum allowable limit of 0.1%, making it non-compliant with soap quality standards